Affective Neuronal Selection: The Nature of the Primordial Emotion Systems - Ellis, George F.; Toronchuk, Judith A. (Frontiers in Psychology, 2013)
Based on studies in affective neuroscience and evolutionary psychiatry, a tentative new proposal is made here as to the nature and identification of primordial emotional systems. Our model stresses phylogenetic origins of emotional systems, which we believe is necessary for a full understanding of the functions of emotions and additionally suggests that emotional organising systems play a role in sculpting the brain during ontogeny. Nascent emotional systems thus affect cognitive development. A second proposal concerns two additions to the affective systems identified by Panksepp. We suggest there is substantial evidence for a primary emotional organising programme dealing with power, rank, dominance and subordination which instantiates competitive and territorial behaviour and is an evolutionary contributor to self-esteem in humans. A programme underlying disgust reactions which originally functioned in ancient vertebrates to protect against infection and toxins is also suggested.